Female Representation in Vocational High School Leadership and Organizational Productivity: A Narrative Study of Women Principals in Gender-Associated School Environments in West Java, Indonesia Introduction - Rizki Satria Nugraha; Aan Komariah; Taufani Chusnul Kurniatun; Abubakar Abubakar; Sururi Sururi (Academic Bright Collaboration, 2026)
Purpose – This study examines how female representation in vocational high school leadership contributes to organizational productivity in gender-associated school environments in West Java, Indonesia. It explores how women principals construct legitimacy, negotiate gendered expectations, enact relational leadership, and support coordination, trust, discipline, communication, and program continuity. Methods – Using a qualitative narrative inquiry design, this study involved six female vocational high school principals selected through criterion-based purposive sampling. Participants held formal principalship positions, had sufficient leadership experience, and led schools where gendered assumptions appeared in fields such as mechanics, automotive, or patisserie. Data were collected through semi-structured narrative interviews and analyzed through repeated reading, narrative coding, cross-case comparison, and thematic interpretation. Findings – Four themes emerged. Leadership legitimacy as a burden of continuous proof shows that women principals repeatedly demonstrated competence and authority to gain recognition. Adaptive relational leadership as organizational coordination indicates that communication, listening, persuasion, and trust-based cooperation strengthened school functioning. Female leadership as representational transformation reveals how women principals challenged gendered assumptions about authority and expanded leadership possibilities. Female leadership as a contributor to institutional productivity shows that women principals supported coordination, communication, discipline, supportive climates, and program continuity. Research Implications – Female leadership should be viewed as both an equality concern and an organizational resource. However, this study is limited by its small sample, West Java context, reliance on narratives, and qualitative interpretation of productivity. Originality: Unlike prior Indonesian studies emphasizing barriers and underrepresentation, this study provides a productivity-oriented narrative account of women principals in gender-associated vocational school environments.